Pemanfaatan MRI Pelvis untuk Memprediksi Kedalaman Infiltrasi Endometriosis Susukan dalam Posterior ke Rektosigmoid: Studi Komparasi - Amelia, Yustie; Muslim, Refni; Marwali, Muhammad Luky Satria; Prawirodihardjo, Bonita; Prihartono, Joedo (Majalah Kedokteran Indonesia, 2019)
Introduction: Rectosigmoid infiltration in posterior deep infiltrating en-dometriosis (DIE) requires radical and interdisciplinary surgery. Standard di-agnostic modalities such as ultrasound and laparoscopy are weak in assesingposterior DIE infiltration to inaccessible areas. MRI has the potential value tobe modality of choice because it is multiplanar and excellent in soft tissuedifferentiation. This study aimed to compare pelvic MRI with surgical findingsand histopathology to predict depth of rectosigmoid infiltration in posteriorDIE. Methods: Thirty-seven patients who underwent surgery and pelvic MRI ex-aminations for posterior DIE at the endometriosis referral center (2015-2018)were studied retrospectively. MRI images were analyzed by a gynecology ra-diologist independently then compared to the surgical report and histopatho-logical analysis. Statistical analysis was performed using the McNemar testand the Cohen’s Kappa coefficient. Results: Concordance values (McNemar p) and Kappa coefficients (p) forassesment of rectosigmoid extension in posterior DIE were 100% (1,000) and1 (0,000); infiltration into themuscular layer of rectosigmoid were 89.2% (0.617)and 0.78 (0.001); infiltration into the (sub)mucosal layer of rectosigmoid were81.1% (1,000) and 0.35 (0.146). Conclusion: There was good concordance between pelvic MRI and surgical-histopathologic findings to predict depth of rectosigmoid infiltration in poste-rior DIE.